MUBALIG YOUTUBE DAN KOMODIFIKASI KONTEN DAKWAH - Ferdi Arifin (al-Balagh : Jurnal Dakwah dan Komunikasi, 2019)
This article attempts to reveal Youtube as a popular social media for da’wa recently. The popularity of da’wa in Youtube generates many celebrity mubalig (islamic preacher). However, the number of mubalig preaching through Youtube also has negative effects. It is caused by each mubalig have different perspectives about Islam teaching, so that the da’wa contents are confusing followers on their perceptions about Islam. Using the Youtube for da’wa media has a good respond, so Youtube channels that upload da'wa content have a large number of viewers and followers. It makes Youtube able to make money through the monetization process. Data collection in this study was carried out through virtual observations on da'wa content of a number of mubalig on Youtube, as well as literature studies to analyze the tendency of da'wa messages on the Youtube channel. As a result, Youtube becomes an alternative media for preaching, even though actually, the commodification of messages emerged through monetization on Youtube.